Differences in Student Activities and Learning Outcomes with the Application of Problem Based Learning assisted by Real Lab and Virtual Lab Media on Salt Hydrolysis Material - Hutabarat, Dina Asima (Universitas Lampung, 2024)
Abstract: Differences in Student Activities and Learning Outcomes with the Application of Problem Based Learning assisted by Real Lab and Virtual Lab Media on Salt Hydrolysis Material. This research aims to determine the differences in student activities and learning outcomes through the application of problem based learning using real and virtual laboratory media laboratory on salt hydrolysis in SMAN 17 Medan. The sample consisted of two classes, namely class XI IPA 2, totaling 32 people as experimental class I and class XI IPA 5, totaling 32 people as experimental class II Random Sampling is specified. Data is collected using test instruments such as achievement tests and non-test instruments, namely student activity observation sheets. Research data uses statistical analysis of the t test (Independent Sample Test). The prerequisite tests are normality and homogeneity tests. The average value of student learning outcomes based on real laboratories is 87.19 and student learning outcomes using virtual laboratories is 81.09. The average value of student learning activities using real lab and virtual lab media is 84.28 and 78.50 respectively. Based on statistical analysis using the t hypothesis test, the calculated t values for learning outcomes and learning activities were 3.43 and 3.63 respectively. This value is located in the H0 rejection area between -2.042 to 2.042. This result shows that there are differences in student activities and learning outcomes through the application of problem based learning with real laboratory media and virtual media salt hydrolysis subject laboratory at SMAN 17 Medan.Keywords: Learning Outcomes, Student Learning Activities, Differences, Problem Based Learning, Real Laboratory, Virtual Laboratory DOI: 10.23960/jppk.v13i2.29976